Factors influencing root canal retreatment strategies by general practitioners and specialists in Australia. (5th July 2014) - Wenteler, G. L.; Sathorn, C.; Parashos, P.
Abstract Aim To evaluate the effect of tooth radiographic features on root canal retreatment strategies used by general dental practitioners and dental specialists in Australia. Methods A descriptive survey study comprising a web‐based questionnaire was sent to general dental practitioners and specialists. The questionnaire diagrammatically represented six different clinical scenarios with variables including type of coronal restoration, quality of root filling and the size and presence of a periapical radiolucency. Treatment options included no treatment, orthograde retreatment, periapical surgery and replacement with an implant. For each of the six scenarios, the participant was asked to select a minimum size cut‐off point where treatment would be initiated and also indicate the preferred treatment option. Results A total of 639 questionnaires were submitted online. In teeth without a cast core restoration, the quality of root filling influenced the selection of no treatment as an option (P < 0.001). The presence of a cast post/core restoration influenced both the treatment cut‐off point and treatment option, with more practitioners selecting larger lesions as cut‐off points (P < 0.001) and more treatment options involving both implant placement (P < 0.001) and periapical surgery (P < 0.001). With more complex treatment planning (i.e. cast post/core restorations and inadequate root filling), general practitioners proposed implant placement more readily compared with specialists (P < 0.001). Conclusions General practitioners and specialists vary their root canal retreatment strategies according to quality of root filling and type of coronal restoration. Whilst all clinical scenarios could be managed by contemporary endodontic techniques, teeth were still treatment planned for extraction and replacement with an implant. This may be due to the fact that implants are heavily marketed by the dental industry and with more stringent outcome criteria applied to the assessment of root canal treatment compared with implant placement, evidence‐based decision‐making may be distorted. Future emphasis should be placed on changing practitioners' attitudes towards the retention of salvageable teeth by contemporary endodontic measures.